The Relationship Between Maternal Motivation And The Role Of Cadres With Adherence To Vitamin A Administration Among Toddlers At The Posyandu In The Working Area Of Puskesmas Watas Marga, 2024 - Rosita, Pera; Putri, Yesi; Jumita, Jumita (Journal of Multidisciplinary Research, 2024)
Deficiency vitamin A deficiency increases the risk of children becoming susceptible to infectious diseases such as upper respiratory tract infections, measles and diarrhoea. Among children among pre-school children there are an estimated 6-7 million new cases of xeropthalmia (night blindness) each year, approximately 10% of which suffer from corneal damage. corneal damage. Among those who suffer corneal damage, 60% die within one year, while among the living 25% become blind and 50-60% half-blind. blind. The aim of the study was to determine the relationship between Mother's Motivation and the Role of Cadres with Adherence to Vitamin A Giving to Toddlers in the Posyandu Watas Marga Health Centre Working Area in 2024. This study This study used analytical research with a cross sectional design. Technique purposive sampling technique, which is sampling based on the consideration of the researcher and in accordance with the inclusion and exclusion criteria. Sample The sample used by mothers had as many as 75 people. Chi-square test results show that the variable of Maternal Motivation with Adherence to Vitamin A Giving to Toddlers is obtained chi-square results p-value 0.001 (α <0.05), the role of cadres with compliancVitamin A administration in toddlers obtained a chi-square p-value of 0.001 (α<0.05), so it can be concluded that there is a relationship between maternal motivation and the role of cadres with adherence to vitamin A administration in toddlers. Cadres with Adherence to Vitamin A Giving to Toddlers in Posyandu Area Watas Marga Health Centre Work Area in 2024. It is recommended that th health centre improve health services, especially in Maternal and Child Health.